2005
DOI: 10.1111/j.1743-6109.2005.20110.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Citrate Response Correlates with the Nature and the Severity of Penile Vascular Insufficiency

Abstract: Introduction Sildenafil citrate is a highly effective erectogenic agent. However, predicting which patients will respond to this agent is often difficult. While the patient response to this agent is dependent on the nitric oxide–guanylate cyclase–cyclic guanosine monophosphate cascade, the integrity of penile arterial flow and venocclusive mechanism is also important. Duplex Doppler penile ultrasonography can reliably document penile hemodynamics. This study aimed at defining response rates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…Moreover, there was neither a right or left preference nor a difference in the right or left penile blood-flow haemodynamics. However, our study presented a similar correlation between PSV, EDF and RI and the clinical efficacy questionnaires in previous studies (Mulhall et al, 2005), which reduces the possibility of a type 1 error. Our research clearly shows that when the highest bilateral and lowest bilateral PSV are considered, the lowest bilateral PSV clearly has a higher correlation with the clinical efficacy, penile rigidity and patient-reported treatment satisfaction (Table 5) When assessing the same variables as predictors of improvement, cure and satisfaction, the lowest PSV shows a fair-to-good ability to predict all three events, while RI on any of the four combinations was a fair predictor of cure and satisfaction, although it was a poor predictor of improvement ( Area under the receiver operating characteristic curve (AUC) are displayed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, there was neither a right or left preference nor a difference in the right or left penile blood-flow haemodynamics. However, our study presented a similar correlation between PSV, EDF and RI and the clinical efficacy questionnaires in previous studies (Mulhall et al, 2005), which reduces the possibility of a type 1 error. Our research clearly shows that when the highest bilateral and lowest bilateral PSV are considered, the lowest bilateral PSV clearly has a higher correlation with the clinical efficacy, penile rigidity and patient-reported treatment satisfaction (Table 5) When assessing the same variables as predictors of improvement, cure and satisfaction, the lowest PSV shows a fair-to-good ability to predict all three events, while RI on any of the four combinations was a fair predictor of cure and satisfaction, although it was a poor predictor of improvement ( Area under the receiver operating characteristic curve (AUC) are displayed.…”
Section: Discussionsupporting
confidence: 83%
“…All the studied penile blood-flow parameters were correlated with clinical efficacy, as already shown in the past by other groups (Mulhall et al, 2005;Xuan et al, 2016), and with treatment satisfaction as assessed by the EDITS questionnaire and VAS. Although correlation was expected (Cappelleri, Tseng, Stecher, & Goldstein, 2018), it had not been demonstrated until now.…”
Section: Discussionmentioning
confidence: 75%
“…In most trials on PDE5 inhibitors, a higher efficacy is usually reported using higher doses of the drug [12]. However, although vardenafil has shown to be overall effective in ED patients independently of baseline severity and etiology [13], the responsivity to PDE5 inhibitors is variable and correlates with nature and severity of penile vascular impairment [14]. In the present study, the apparently surprising result that, at the endpoint, the highest efficacy occurred in patients taking the lowest dose of the drug can be explained bearing in mind that a dose‐titration strategy has been adopted in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The common underlying vascular abnormalities were corporal VOD alone or combined with arterial insufficiency. These abnormalities were the causes of failure, and are very difficult to treat, as those cases were predicted to be non-responders according to Mullhall et al [19]; they stated that the presence of any degree of venous leak resulted in reduced efficacy of sildenafil, with only five of 46 (11%) patients responding to sildenafil. Also, corporeal VOD alone or combined with arterial disease is the specific haemodynamic abnormality causing no response to intracavernous pharmacotherapy [18].…”
Section: Discussionmentioning
confidence: 99%